The Social and Psychological Impact of Muhallil Marriage on Women from an Islamic Legal Perspective - Eka Wulandari; Rizki Septian (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2020)
This research examines the social and psychological impacts experienced by women in the practice of nikah muhallil and evaluates the role of Islamic law in providing protection for them. Through a qualitative approach involving in-depth interviews and case studies, this research found that women involved in nikah muhallil often face social stigma, psychological pressure, and a lack of understanding and access to legal aid. The research results show that the practice of nikah muhallil causes significant emotional instability and social isolation for women. In addition, this research reveals differences in views between schools of thought regarding the validity of muhallil marriages, which adds to the complexity and ambiguity of the law. The proposed recommendations include increased public education and awareness, stricter law enforcement, and the provision of comprehensive support services for affected women. Clearer and firmer legal reforms are needed to ensure the protection of women's rights and improve their social and psychological well-being in the context of Islamic marriage.